Pengaruh Pengawasan Inspektorat Terhadap Kinerja Pegawai Di Kabupaten Tapanuli Tengah - Sitorus, Monang (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2011)
The aim of this research was to analyze the influence of controlling function by Inspectorate’s in improving the performance of civil servants (Case study of Regency Tapanuli Tengah). The concept of controlling used Robbins and Coulter’s (2006) theorywhich consists of three dimensions namely (1) standard; (2) measurement; and comparison; (3) action. The performance concept used Mitchell’s (1985: 391) theory which consists of two dimensions (1) ability; and (2) motivation. These three controlling dimension were applied to analysis performance apparatus in Regency Tapanuli Tengah. To indentify the three influence of dimension, a survey approach was conducted through a proportional sample of 144. The data were analyzed using Path Analysis, in the LISREL (Linear Structural Relation) program. The value was found out each dimension as follows; (a). Influence standard (X1) to performance apparatus (Y) is 0.362 (low category), influence measurements and comparison (X2) to performance apparatus (Y) is 0.371 (low category), influence action (X3) to performance apparatus (Y) is 0.251 (very low category). The effect (X1, X2, X3) to Y is 69.62% (strong category, and the residual is 30.38% influenced the other dissimilar factor (epsilon).